(untitled) (Journal of Bio-Science, 2018)
Cancer is a class of diseases in which a group of cells display uncontrolled growth, invasion and sometimes metastasis. In order to find out a new anticancer drug, Ni(II) complex with benzoin thiosemicarbazon was synthesized and characterized. Anticancer activities of Ni(BTSC)2 2 2 has been studied against Ehrlich Ascites Carcinoma (EAC) cells in Swiss albino mice by monitoring tumor cell growth inhibition, tumor weight measurement, survival time of tumor bearing Swiss albino mice. Hematological parameters were also studied in both normal and EAC bearing treated mice. The results were compared with those obtained with a standard anticancer drug bleomycin and the compound was found to possess pronounced anticancer effect. Maximum cell growth inhibition was found to be 77.15% after treatment with Ni(BTSC)2 at the dose of 8 mg/kg (i.p). About 69.56% enhancement of life span was found at 8 mg/kg (i.p).With the same dose Ni(BTSC)2 reduced the tumor weight by 52.17% at day 20. The hematological parameters (WBC, RBC, hemoglobin content and differential counts) were found to be significantly changed as compared to those of the normal mice. These parameters restored more or less towards normal when treated with the test compound. J. bio-sci. 23: 77-88, 2015